“Natural Wealth” as a Legal Category: Debatable Questions - A. P. Anisimov; S. V. Narushkevich (Сибирское юридическое обозрение, 2018)
The article proves that “natural wealth” is a term of Russian constitutional law that has no implementation mechanism in sectoral (environmental) legislation and only duplicates the term “natural resources” including all components of the natural environment (land, water, forests, etc.), which can be used in economic activities. Since the term “natural wealth” does not carry any independent meaning, it is necessary to exclude from Art. 58 of the Constitution of the Russian Federation the mentioning of the need to “take care of natural resources”.In addition, the authors of the Federal Law “On Environmental Protection” propose to exclude rules obliging citizens to protect natural resources, since this obligation is implemented through a number of more specific rules on the protection of natural resources and objects.